2014
DOI: 10.1177/1471301214539956
|View full text |Cite
|
Sign up to set email alerts
|

Coping with cognitive impairment and dementia: Rural caregivers’ perspectives

Abstract: Caregiving in a rural context is unique, but the experience of rural caregivers is understudied. This paper describes how rural caregivers cope with caring for a loved one diagnosed with mild cognitive impairment or dementia using qualitative description to generate a low-inference summary of a response to an open-ended question. This approach allowed these rural caregivers to describe their positive experiences in addition to the more commonly explored caregiver experiences related to stress. Analyses of copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
(91 reference statements)
1
15
1
Order By: Relevance
“…The findings of the present study illustrated that more than one-quarter and onefifth of the caregivers respectively usually use exercises and Self-distraction to overcome stressors situations and burden of caregiving this was in agreement with the study of (73) in Canda who revealed that more than onethird and less than onethird of caregivers respectively usually used self-Physical activities and restructuring to cope with the burden.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study illustrated that more than one-quarter and onefifth of the caregivers respectively usually use exercises and Self-distraction to overcome stressors situations and burden of caregiving this was in agreement with the study of (73) in Canda who revealed that more than onethird and less than onethird of caregivers respectively usually used self-Physical activities and restructuring to cope with the burden.…”
Section: Discussionsupporting
confidence: 92%
“…Rural communities can also be important sources of social opportunities and meaningful relationships (Keating et al, 2013). Despite fragmented formal support, family carers and people with dementia may draw on positive aspects of rural environments (Egdell et al, 2010) to develop protective coping strategies even in difficult circumstances (Branger et al, 2016). This may explain the absence of significance on the rural-urban variable in our study.…”
Section: Discussionmentioning
confidence: 76%
“…In spite of these challenges, people with dementia and their partners actively negotiate the support required to cope with and care for dementia, drawing on positive aspects of rural environments (Blackstock et al 2006; Egdell et al 2010) and developing adaptive coping strategies to meet the demands of care (Branger et al 2014). More information is needed, however, about the place-specific transitions and trajectories of partners in care to help support them and the person with dementia over the course of the condition (Forbes et al 2012).…”
Section: Introductionmentioning
confidence: 99%